2019
DOI: 10.1016/j.neulet.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of serine 305 in tau inhibits aggregation

Abstract: Alzheimer's disease and other tauopathies are characterized by the brain accumulation of hyperphosphorylated aggregated tau protein forming pathological inclusions. Although elevated tau phosphorylated at many amino acid residues is a hallmark of pathological tau, some evidence suggest that tau phosphorylation at unique sites, especially within its microtubule-binding domain, might inhibit aggregation. In this study, the effects of phosphorylation of two unique residues within this domain, serine 305 (S305) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…The sequence recognized by AT100 and pS396 antibodies is conserved in human and in Syrian hamster-a small mammal with the capacity to hibernate under adverse conditions [51], which suggests that these phosphorylations could also be reversed in AD cases. In others studies, it has been described that phosphorylation of tau on threonine 205 may have a protective role by preventing A␤-induced excitotoxicity [52] and that serine 305 phosphorylation inhibits tau aggregation [53]. In addition, in vitro experiments revealed that phosphorylation of threonine 212 may inhibit the toxic aggregation of tau [23].…”
Section: Discussionmentioning
confidence: 96%
“…The sequence recognized by AT100 and pS396 antibodies is conserved in human and in Syrian hamster-a small mammal with the capacity to hibernate under adverse conditions [51], which suggests that these phosphorylations could also be reversed in AD cases. In others studies, it has been described that phosphorylation of tau on threonine 205 may have a protective role by preventing A␤-induced excitotoxicity [52] and that serine 305 phosphorylation inhibits tau aggregation [53]. In addition, in vitro experiments revealed that phosphorylation of threonine 212 may inhibit the toxic aggregation of tau [23].…”
Section: Discussionmentioning
confidence: 96%
“…This may help to explain why Tau is prone to self-assemble and co-aggregate in some cases of Lewy body-associated diseases. In addition to S129, several other phosphorylation sites were identified within or adjacent to the binding interface of α-syn and K19, including Y125 and Y136 in α-syn as well as S320 in K19 (54,55). Further research is warranted to clarify how such modifications, as well as disease familial disease-associated mutations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Triple phosphorylation at Ser202/Thr205/Ser208 has been proposed to be a combination that leads to rapid tau aggregation [ 51 , 77 ]. On the other hand, phosphorylation sites such as Ser214, Ser262, and Ser305 have been demonstrated to inhibit tau aggregation and may be neuroprotective [ 78 , 79 ]. In late disease stages, the hyperphosphorylation of multiple pro-aggregation sites may overcome protective ones.…”
Section: Main Textmentioning
confidence: 99%